2010
DOI: 10.1021/jf903334g
|View full text |Cite
|
Sign up to set email alerts
|

Dammarane-Type Saponins from the Flower Buds ofPanax ginsengand Their Intracellular Radical Scavenging Capacity

Abstract: Korean ginseng (Panax ginseng C.A. Meyer) has been extensively used as a functional food for thousands of years. This study with the aim to evaluate the potential of P. ginseng flower components as a functional food with medicinal properties resulted in the identification of three new dammarane-type saponins, named floralginsenosides Ka-Kc (1-3), along with seventeen known ones (4-20). Their structures were elucidated on the basis of chemical and spectroscopic methods, and their antioxidant activities were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 23 publications
0
32
0
1
Order By: Relevance
“…Many flavonoids have exhibited a range of biological and pharmacological effects including antioxidant property and inhibition of free radical-mediated processes (Facino et al, 1990;Mora et al, 1990;Yen and Chen, 1995;Cao et al, 1997;Cos et al, 1998). Recently, saponins have also been shown to possess potent antioxidant properties (Fu et al, 2009;Gupta et al, 2009;Kim et al, 2009;Nzowa et al, 2010;Tung et al, 2010). So, plants containing flavonoids and/or saponins may be potential source of new antioxidant with less pro-oxidant effects.…”
Section: Introductionmentioning
confidence: 99%
“…Many flavonoids have exhibited a range of biological and pharmacological effects including antioxidant property and inhibition of free radical-mediated processes (Facino et al, 1990;Mora et al, 1990;Yen and Chen, 1995;Cao et al, 1997;Cos et al, 1998). Recently, saponins have also been shown to possess potent antioxidant properties (Fu et al, 2009;Gupta et al, 2009;Kim et al, 2009;Nzowa et al, 2010;Tung et al, 2010). So, plants containing flavonoids and/or saponins may be potential source of new antioxidant with less pro-oxidant effects.…”
Section: Introductionmentioning
confidence: 99%
“…Biologically active constituents of ginseng have been pursued extensively and many dammarane-type triterpene oligoglycosides, generally known as ginsenosides, have been characterized as the principal (Shibata, 2001;Park et al, 2005). In our research on ginseng leaves and flowers, it is recognized that the leaves and flowers have been rich in also various ginsenosides (Tung et al, 2009(Tung et al, , 2010a. Furthermore, our recent study concerning processed leaves and flowers in respect to that of ginseng roots in traditional use resulted in the identification of series of unique ginsenosides, including notoginsenoside R 10 (1), ginsenoside Rg 3 (2), ginsenoside ST 2 (3), ginsenoside ST 1 (4), ginsenoside Rh 1 (5), 20S-ginsenoside Rg 2 (6), 20R-ginsenoside Rg 2 (7), ginsenoside SL 2 (8), ginsenoside SL 3 (9), ginsenoside SL 1 (10), ginsenoside SF (11), ginsenoside Rg 6 (12), ginsenoside F 4 (13), ginsenoside Rh 3 (14), ginsenoside Rk 2 (15), 20S-ginsenoside Rh 2 (16), 20R-ginsenoside Rh 2 (17), ginsenoside Rs 4 (18), pseudoginsenoside RC 1 (19), 6'-acetyl-ginsenoside Rg 1 (20), and ginsenoside Mb (21) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…22 In particular, studies found that deglycosylated ginsenosides Rg 3 , Rk 1 , and Rg 5 possessed a stronger antioxidative capacity than PPD or PPT.…”
mentioning
confidence: 99%